White Spot Syndrome Virus Envelope Protein VP 53 B Functions as a Trypsin Inhibitor and Interacts With Hemocyanin - Wenxu Xia; Lingqi Zhuang; Yuchen Liu; Kai Li; Bing Qin; Shuling Yan; Yongxin Yu; Yongjie Wang (Journal of Fish Diseases, 2026)
White spot syndrome virus (WSSV) remains a persistent and significant threat to the global shrimp aquaculture industry. However, its pathogenic mechanisms remain incompletely understood, and no effective intervention strategies are currently available. In this study, we investigated the functional role of VP53B, an envelope structural protein of WSSV, using a combination of infection bioassays, protein structure prediction, protease inhibition assays and protein binding analyses. Our results demonstrate that VP53B is a critical determinant of per os (oral) infection in shrimp, including Procambarus clarkii (crayfish) and Litopenaeus vannamei (whiteleg shrimp). Functionally, VP53B acts as a trypsin inhibitor and interacts with host hemocyanin. We propose that through modulation of shrimp trypsin and hemocyanin, VP53B disrupts the prophenoloxidase‐activating system, a key innate immune pathway, thereby facilitating successful WSSV infection. This study provides new insights into the molecular mechanisms underlying WSSV oral infectivity and highlights VP53B as a potential target for therapeutic intervention.